Pengembangan Alat Permainan Edukatif Dengan Barang Bekas Untuk Mengembangkan Bahasa Anak Usia Dini - Puspita, Yenda; Muthmainah, Muthmainah; Joni, Joni; Yusi Nur Sa'ida, Amin (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
This study aims to develop educational play equipment (APE) made from recycled materials as a learning medium that can support the language development of early childhood at Pembina 2 Pekanbaru State Kindergarten. The research method used is Research and Development (R&D) with the Borg and Gall development model. The resulting product is a learning medium made from recycled materials designed to stimulate children's language skills. The results of the study indicate that this learning medium is considered feasible and practical for use by experts, teachers, and students. These findings confirm that the recycled material-based media developed is effective in supporting the improvement of early childhood language skills while instilling the values ​​of creativity and environmental awareness